CTCF-silenced miR-137 contributes to EMT and radioresistance in esophageal squamous cell carcinoma - Xu, Shuwen (Cancer Cell Int, 2021)
BACKGROUND: Esophageal squamous cell carcinoma (ESCC) is one of the most malignant tumors in gastrointestinal system. MicroRNAs (miRNAs) have been reported to be implicated in cancer development. However, the role of miR-137 has not been fully revealed in ESCC. METHODS: Quantitative real-time polymerase chain reaction (qRT-PCR) and western blot analyses were separately used to examine RNA level and protein level. 5-ethynyl-2′-deoxyuridine (EdU) assay, transwell assays and flow cytometry analyses were conducted to assess biological behaviors of ESCC cells. Additionally, the interaction between genes were analyzed via Chromatin Immunoprecipitation (ChIP) assay, RNA Binding Protein Immunoprecipitation (RIP) assay, RNA pull down assay and luciferase reporter assay. RESULTS: MiR-137 was down-regulated in ESCC cells. Upregulation of miR-137 hindered ESCC cell proliferation, migration, invasion and epithelial mesenchymal transition (EMT). Besides, miR-137 enhanced the sensitivity of ESCC cells to irradiation. Moreover, CCCTC-binding factor (CTCF) inactivated miR-137 transcription in ESCC cells. Furthermore, we revealed enhancer of zeste 2 polycomb repressive complex 2 subunit (EZH2) and paxillin (PXN) as the downstream targets of miR-137. In turn, EZH2 was recruited by CTCF and induced methylation in miR-137 promoter. CONCLUSION: CTCF/Suz12/EZH2 complex-silenced miR-137 facilitates ESCC progression and radioresistance by targeting EZH2 and PXN.